Imaging Diagnosis, Prevalence, and Clinical Outcomes of Arthroscopic Surgery for Anterior Inferior Iliac Spine Impingement: A Systematic Review and Meta-analysis. Issue 11 (9th November 2022) - Kobayashi, Naomi; Kamono, Emi; Yamamoto, Yuya; Yukizawa, Yohei; Honda, Hideki; Takagawa, Shu; Misumi, Toshihiro; Inaba, Yutaka
Background: Subspine impingement, or anterior inferior iliac spine (AIIS) impingement, is a type of extra-articular pathology associated with femoroacetabular impingement syndrome and often requires subsequent arthroscopic surgery. Purpose: To examine the diagnostic accuracy, prevalence, and clinical outcomes of arthroscopic treatment for AIIS impingement. Study Design: Systematic review; Level of evidence, 4. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 checklist was applied. We searched for studies on the prevalence, diagnostic accuracy, and results of surgical treatment for AIIS impingement. For each included study, data synthesis and statistical analysis were performed to identify pooled prevalence, calculate clinical outcome scores, and estimate adverse events. The QUADAS (a quality assessment tool for diagnostic accuracy studies) was used to assess the quality of the diagnostic accuracy studies, and the Risk of Bias Assessment tool for Nonrandomized Studies was used to assess the quality of the studies on arthroscopic treatment efficacy. Results: Out of an initial 791 studies, 23 were included. AIIS impingement was diagnosed by plain radiography with 76% to 86% sensitivity, 3-dimensional computed tomography with 80% to 81.8% sensitivity, magnetic resonance imaging with 80% sensitivity, and ultrasound with 92.5% sensitivity. For patients who underwent hip arthroscopy, the pooled prevalence of AIIS impingement was 18%. Significant improvement between pre- and postoperative clinical outcomes was observed: 25.75 points for the modified Harris hip score (mHHS), 46.88 points for the Hip Outcome Score–Sport subscale, 20.85 points for the Nonarthritic Hip Score, and -2.92 points for the pain visual analog scale. The minimal clinically important difference on the mHHS was exceeded by 94% of patients. The pooled incidence of surgical complications was 1%. Of 6 included studies on diagnostic accuracy, 2 were identified as having a low risk of bias, and 4 included >2 factors with a high risk of bias. All 9 included studies on treatment outcomes had at least 1 factor with a high risk of bias. Conclusion: Several imaging modalities assist in the diagnosis of AIIS impingement. The overall prevalence of AIIS impingement in patients that underwent hip arthroscopy was 18%. Clinical outcomes after arthroscopic AIIS decompression were generally favorable, with a relatively low rate of surgical complications.